Celia simplified the expression Negative 4 x (1 minus 3) minus (2 x + 2). She checked her work by letting x = 5 in both expressions. Her work for the original expression is shown below.

Negative 4 x (1 minus 3) minus (2 x + 2) = negative 4 (5) (1 minus 3) minus (2 (5) + 2) = negative 20 (negative 2) minus 12 = 40 minus 12 = 28.


Celia knows that the simplified expression should also equal 28 when x = 5. Which shows Celia’s simpllifed expression?

Respuesta :

Answer:

-4x (1-3) - (2x + 2)

-4(5)(1-3) - (2(5) + 2)

-20(1-3) - (10 + 2)

-20(-2) - (12)

40 - (12)

28

Step-by-step explanation:

ACCESS MORE